Os gêneros multimodais nos livros didáticos de história : um estudo crítico-dialógico - Benevides, Louredir Rodrigues (2015)
This research has the aim to discuss about the activities composed of multimodal genres from one serie of History´s textbook for Secondary Level used by public state schools in the city from Campo Verde – Mato Grosso. Therefore, it underlies upon the theoretical framework of teaching and learning reading in the light of New Literacies Studies (STREET, 1996) and visual literacy (KRESS, VAN LEEUWEN, 1996). As well as, we used the concepts from utterance, discourse, speech genres and discoursive domains of production, circulation and reception from Bakhtin´s Circle (BAKHTIN, 1929; 1952; 1952-1953/1979; 1973/1975; BAKHTIN/VOLOCHINOV, 1929), resignified as multimodal genres in light of the theoretical perspective of Pedagogy of multiliteracies (THE NEW LONDON GROUP, 1996). Furthermore, we also anchored on the assumptions from Paes de Barros (2005; 2009), in dealing with multimodal texts reading skills, applied to the understanding of composite activities of visual texts in the textbook serie studied. Also in Vygotsky, we find the socio-historical theoretical framework (VYGOTSKY, 1930; 1933), in particular, their weightings about History teaching and learning (VYGOTSKY, 1926). From socio-historical nature also are the constructs of critical literacy in a contemporary rereading of Freire (1970; 1979;1981). The methodological course was traced on quantitative and qualitative nature since the multimodal genres were initially quantified, whose highest incidences indicate the predominance of painting reproductions and photographs, where as qualitative analysis revealed his employment over the basic levels of multimodal texts reading skills because these genres in the three observed volumen, are used for more as illustrations of historical knowledge and, consequently, they do not advance to other dimensions of multimodality observation strategies (PAES DE BARROS, 2009). We conclude that the composed activities of multimodal genres do not contribute to the development of visual and critical literacies, for the reason that they are limited mostly to the use of images as illustration of verbal texts, and consequentely, they failed to promote critical reflection on these important texts in the present time.